Pelatihan Budidaya Larva Lalat Buah Sebagai Pakan Alternatif Produksi Tambak Ikan di Kabupaten Pangkep - Andi Yunarni Yusri; Khaerun Nisa'a Tayibu; Andi Zam Immawan Alam (Jurnal Pengabdian UNDIKMA, 2023)
This service activity aims to increase the knowledge and skills of fish farming residents regarding cultivating fruit fly larvae (BSF maggots) as an alternative feed for fish pond production in Pangkep Regency. Implementing this service used training and assistance in making alternative feed products. The evaluation instrument for this activity was an interview guide and practice, then analyzed descriptively. This activity showed that training activities on cultivating fruit larvae as alternative feed provided benefits and positive impacts for fish farmers, where farmers could make an alternative feed from fruit fly larvae that was cheaper and had high nutritional value.